О влиянии угла скоса опорных поверхностей зубцов хвостовых соединений лопаток турбин на характер их напряженного состояния - Шубенко, А. Л.; Сухинин, В. П.; Фурсова, Т. Н.; Бояршинов, В. Ю. (НТУ "ХПИ", 2012)
Для многоопорного елочного хвостового соединения высоконагруженных рабочих лопаток паровых турбин рассмотрено влияние угла скоса опорных поверхностей зубцов на характер его напряженного состояния.

For multisupporting fir-tree tail connection of high-rate working shoulder-blades of steam-turbines influence of corner of slant of underlayments of indents is considered on character of his tense state.
About influence of corner of slant of underlayments of indents of tail connections of shoulder-blades of turbines on character of their tense state
Keywords: турбина; лопатка; угол скоса